700 Skarabäen und Verwandtes aus Palästina/Israel Die Sammlung Keel - Keel, Othmar (Orbis Biblicus et Orientalis. Series Archaeologica, 2020)
The scarabs and related seal amulets published here form a collection that was assembled between 1975 and 2012 during work on the author's Corpus of stamp-seal amulets from Palestine/Israel. The aim was to prevent numerous unusual and interesting pieces disappearing from view in unpublished private collections or as items of jewellery, and to guarantee researchers and the public continuing access to them. The 700 pieces were selected in such a way that the most significant groups and motifs that were produced in or imported into Canaan/Palestine are represented and, collectively, form a kind of textbook on the subject. In that respect, the collection and this catalogue are both unique.